2014
DOI: 10.1155/2014/729618
|View full text |Cite
|
Sign up to set email alerts
|

Description of a Novel Adhesin ofMycobacterium aviumSubsp.paratuberculosis

Abstract: The binding and ingestion of Mycobacterium avium subsp. paratuberculosis (MAP) by host cells are fibronectin (FN) dependent. In several species of mycobacteria, a specific family of proteins allows the attachment and internalization of these bacteria by epithelial cells through interaction with FN. Thus, the identification of adhesion molecules is essential to understand the pathogenesis of MAP. The aim of this study was to identify and characterize FN binding cell wall proteins of MAP. We searched for conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…EF-Tu is also identified as a major cell surface protein in Mycobacterium leprae (Marques et al, 1998 ). The ability of EF-Tu to function as a fibronectin-binding protein in several bacterial pathogens, including M. pneumoniae (Balasubramanian et al, 2008 ), Streptococcus suis (Li et al, 2015 ), and Mycobacterium avium (Viale et al, 2014 ), provided evidence of its biological versatility. A previous study and our flow cytometry analysis confirmed the membrane distribution of EF-Tu in M. hyopneumoniae (Reolon et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…EF-Tu is also identified as a major cell surface protein in Mycobacterium leprae (Marques et al, 1998 ). The ability of EF-Tu to function as a fibronectin-binding protein in several bacterial pathogens, including M. pneumoniae (Balasubramanian et al, 2008 ), Streptococcus suis (Li et al, 2015 ), and Mycobacterium avium (Viale et al, 2014 ), provided evidence of its biological versatility. A previous study and our flow cytometry analysis confirmed the membrane distribution of EF-Tu in M. hyopneumoniae (Reolon et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also an adhesion/invasion factor secreted by microbes during infection by bacteria (like Helicobacter pylori) (Chiu, Wang, Tsai, Lei, & Liao, ) and fungi (Marcos et al., ) through binding ( Mycobacterium avium subsp. paratuberculosis ) with fibronectin on host cells (Viale et al., ). Superoxide dismutases (SODs) protect the bacteria from oxidative damage by converting endogenously generated superoxide radicals into hydrogen peroxide and oxygen, are indispensable for intraphagocytic viability for pathogenic bacteria (Dhar, Gupta, & Virdi, ), SodB is required for colonization of Helicobacter pylori in the stomach (Tsugawa et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…paratuberculosis to attach and invade two epithelial cell lines (Secott et al, 2002) but the identity of bacterial cell surface receptor(s) for Fn were not known. EF-Tu is a surface exposed cell wall protein in Mycobacterium avium subspecies paratuberculosis (MAP) (Viale et al, 2014). With the importance of Fn to MAP adhesion and invasion (Secott et al, 2002), and as EF-Tu is known to bind Fn in M. pneumoniae (Dallo et al, 2002; Balasubramanian et al, 2008) and A. baumannii (Dallo et al, 2012), it was investigated for its role as a Fn-binding protein.…”
Section: Moonlighting Proteins In Bacteriamentioning
confidence: 99%